Basics of qualitative research techniques and procedures for developing grounded theory. - Corbin, Juliet M., 1942-; Strauss, Anselm L. (Los Angeles, [Calif.] ; London : SAGE, 2008)
This edition takes the form of an informal dialogue, akin to students and teachers working together in a classroom. It shows the evolution of grounded theory method over time and the influence of constructionists and post-modern trends.
Previous ed.: published as by Anselm Strauss, Juliet Corbin. 1998.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research; Social sciences -- Methodology